2016
DOI: 10.19126/suje.46187
|View full text |Cite
|
Sign up to set email alerts
|

Predict-Observe-Explain Tasks in Chemistry Laboratory: Pre-Service Elementary Teachers’ Understanding and Attitudes

Abstract: This study was conducted to investigate the effects of laboratory activities based on predictobserve-explain tasks related to the subjects of "Mixtures, Physical and Chemical Changes, Acids and Bases" on pre-service elementary teachers' understanding and attitude toward chemistry lesson and chemistry laboratory. For this purpose, the pre-service elementary teachers were randomly assigned to experimental (N=26) and control (N=30) groups. The experimental group was instructed using laboratory activities based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Duration and concept/unit selection were also the limitations of the current study. Despite the findings of these studies, there exist other studies that revealed positive effects of POE on students' attitudes towards science (Acar Şeşen & Mutlu, 2016;Erdem Özcan, 2019). In those studies, the implementation lasted about eight to ten weeks, which may be considered as a reason for the improvement in students' attitudes.…”
Section: Discussionmentioning
confidence: 92%
“…Duration and concept/unit selection were also the limitations of the current study. Despite the findings of these studies, there exist other studies that revealed positive effects of POE on students' attitudes towards science (Acar Şeşen & Mutlu, 2016;Erdem Özcan, 2019). In those studies, the implementation lasted about eight to ten weeks, which may be considered as a reason for the improvement in students' attitudes.…”
Section: Discussionmentioning
confidence: 92%
“…POE is constructivism-based learning that helps build students' cognitive structures. POE engages students in developing ideas through "predicting" activities, exploring the sources of knowledge through investigation, reflecting ideas, and conducting meaningful discussions through "explain" actions (Şeşen & Mutlu, 2016).…”
Section: Predict Observe Explainmentioning
confidence: 99%
“…In POE, students are encouraged to discuss arguments, increase the level of student information, and concept understanding. POE is useful in developing students' ideas and skills (Şeşen & Mutlu, 2016). POE accommodates meaningful learning that can build students' scientific attitudes as well as motivation (Bilen et al, 2016).…”
Section: Predict Observe Explainmentioning
confidence: 99%
“…One of the obstacles faced came from the teachers in elementary schools. Many teachers have misconceptions about a subject matter, one of which is the basic concept of natural science Many factors can be a source of misconceptions for prospective teacher students, including (1) prior knowledge, (2) daily life experiences, (3) language, culture, teacher, textbooks, and (4) learning (Cetin et al, 2015). That is, a teacher and the learning process carried out can also cause misconceptions among students.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another study suggests that the POE strategy can also correct the misconceptions of prospective teachers and teachers (Afacan & Gürel, 2019). Laboratory activities based on Predict Observe Explain (POE) are also considered to improve and improve the understanding and attitudes of prospective teachers compared to traditional learning (Acarsesen & Mutlu, 2016;Gernale et al, 2015;Hilario, 2015).…”
Section: Introductionmentioning
confidence: 99%